2021
DOI: 10.3389/fncel.2020.559182
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Enriched Environment Ameliorates the Accelerated Age-Related Memory Impairment Induced by Gestational Administration of Lipopolysaccharide: Role of Plastic Mitochondrial Quality Control

Abstract: Studies have shown that gestational inflammation accelerates age-related memory impairment in mother mice. An enriched environment (EE) can improve age-related memory impairment, whereas mitochondrial dysfunction has been implicated in the pathogenesis of brain aging. However, it is unclear whether an EE can counteract the accelerated age-related memory impairment induced by gestational inflammation and whether this process is associated with the disruption of mitochondrial quality control (MQC) processes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 85 publications
2
27
0
Order By: Relevance
“…This is likely caused by effects of EE on neuroplastic responses to injury. The finding that an EE can reduce the cognition impairment of SAE is in accord with similar observations in animals with other forms of brain dysfunction [43][44][45][46][47][48]. Healthy environments also afford similar benefits to humans.…”
Section: Discussionsupporting
confidence: 82%
“…This is likely caused by effects of EE on neuroplastic responses to injury. The finding that an EE can reduce the cognition impairment of SAE is in accord with similar observations in animals with other forms of brain dysfunction [43][44][45][46][47][48]. Healthy environments also afford similar benefits to humans.…”
Section: Discussionsupporting
confidence: 82%
“…Several findings have indicated that EE improves activity-dependent synaptic plasticity, LTP, social interaction, and spatial learning and memory in models of Alzheimer’s disease, brain injury, Parkinson’s disease, and schizophrenia (Murueta-Goyena et al, 2019 ). Our lab has also shown that long-term EE attenuates the exacerbated age-related cognitive impairment induced by lipopolysaccharide exposure during pregnancy (Zhuang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 87%
“…The Western blotting procedure was performed as previously described (Zhuang et al, 2021 ). Hippocampal tissue was lysed in RIRA lysis buffer, and protein concentrations were determined using a BCA Protein Assay Kit.…”
Section: Methodsmentioning
confidence: 99%
“…However, escape latency can be affected by the swimming speed of mice. Because the swimming distance can better reflect the learning ability of aged mice in the learning phase ( Zhang et al, 2020 ), the swimming distance was preferentially used as an indicator of learning performance of mice in the present study, and the percentage of swimming distance and time in the target quadrant was recorded to evaluate the level of memory consolidation, as per previous studies ( Wu et al, 2020 ; Zhuang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%